Liquidity of the CBOE Equity Options - VIJH, ANAND M. (Journal of Finance, 1990)
ABSTRACT We examine the CBOE option market depth and bid‐ask spreads. Absence of price effects surrounding large option trades suggests excellent market depth. However, bid‐ask spreads for the CBOE options and the NYSE stocks are nearly equal, even though an average option is equivalent to less than half a stock plus borrowing. We explain this tradeoff between market depth and bid‐ask spreads on the CBOE and the NYSE by differences in market mechanisms. We also show that the adverse‐selection component of the option spread, which measures the extent of information‐related trading on the CBOE, is very small.